Development and clinical validation of loop-mediated isothermal amplification (LAMP) assay to diagnose high HBV DNA levels in resource-limited settings. (December 2021) - Vanhomwegen, Jessica; Kwasiborski, Aurélia; Diop, Abou; Boizeau, Laure; Hoinard, Damien; Vray, Muriel; Bercion, Raymond; Ndiaye, Babacar; Dublineau, Amélie; Michiyuki, Satoru; Manuguerra, Jean-Claude; Sauvage, Virginie; et al.
Abstract: Objective: A massive scale-up of testing and treatment is indicated to globally eliminate hepatitis B virus (HBV) infection. However, access to a polymerase chain reaction (PCR), a key test to quantify HBV DNA levels and determine treatment eligibility, is limited in resource-limited countries. We have developed and evaluated the loop-mediated isothermal amplification (LAMP) assay to diagnose clinically important HBV DNA thresholds defined by the WHO (≥20 000 and ≥ 200 000 IU/mL). Methods: Pan-genotypic primer sets were designed on conserved HBV gene regions. Accuracy of LAMP to identify highly viraemic patients was evaluated in 400 and 550 HBV-infected people in France and Senegal, respectively. Results: Our primers successfully detected eight major HBV genotypes/sub-genotypes (A1/2/3 /B/C/D/E/F) with a detection limit ranging between 40 and 400 IU/mL. In France, the area under the receiver operating characteristic curve (AUROC), sensitivity and specificity of bead-based extraction and real-time turbidimetric LAMP were 0.95 (95% CI 0.93–0.97), 91.1% and 86.0%, respectively, to diagnose HBV DNA ≥20 000 IU/mL; and 0.98 (0.97–0.99), 98.0% and 94.6% for ≥200 000 IU/mL. The performance did not vary by viral genotypes. In Senegal, using a field-adapted method (reagent-free boil-and-spin extraction and inexpensive end-point fluorescence detection), the AUROC, sensitivity and specificity were 0.95 (0.93–0.97), 98.7% and 91.5%, respectively, to diagnose HBV DNA ≥200 000 IU/mL. The assay was not adapted to discriminate low-level viraemia. Discussion: We have developed a simple, rapid (60 min), and inexpensive (US8/assay) alternative to PCR to diagnose high viraemia ≥200 000 IU/mL. HBV-LAMP may contribute to eliminating HBV mother-to-child transmission by identifying high-risk pregnant women eligible for antiviral prophylaxis in resource-limited countries.